In search for enterprise: State-sector reform and societal transformation in China - John Hassard; Jackie Sheenan; Jonathan Morris; Xiao Yuxin (Journal for East European Management Studies, 2001)
With special reference to the steel industry, this article draws upon a politicalinstitutional perspective to examine the progress made in the most recent round of state-enterprise reform in China - the introduction of the Modern Enterprise System and Group Company System. This reform programme is intended, by 2010, to transform 156 of China's largest state-owned enterprises (SOEs) into internationally competitive corporations which, while still remaining in overall state ownership, will much more closely resemble typical Western corporations in their structures and processes, with Boards of Directors accountable to shareholders rather than being subject to the political authority of the Chinese Communist Party (CCP). – – Unter besonderer Berücksichtigung der Stahlindustrie wird in dieser Arbeit untersucht, welche Fortschritte in der aktuellen Phase der Reform der Staatsunternehmen in China, also bei der Einführung des Modern Enterprise System und des Group Company System, gemacht wurden. Ziel dieses Reformprogramms ist die Transformation von 156 der größten chinesischen Staatsunternehmen in international wettbewerbsfähige Unternehmen bis zum Jahre 2010. Obwohl die Unternehmen in Staatseigentum bleiben, werden sie strukturell viel stärker an westliche Unternehmen erinnern. Rechenschaft muss dann gegenüber den Anteilseignern abgelegt werden; die kommunistische Partei Chinas wird in diesen umstrukturierten Unternehmen keine politische Autorität mehr ausüben.
Keywords: 650